Teacher Communication Construction: Strategies for Shaping Santri's Religious Moderation Attitudes at Madrasah Ulumul Qur’an Langsa, Aceh - Sanusi Sanusi; Syuknura Magfirah (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2026)
Previous studies on religious moderation in Islamic boarding schools largely focus on policy and curriculum, rarely examining how teachers construct Islamic communication to shape students' attitudes across cognitive, affective, and conative domains. This study aims to analyze the construction of Islamic communication by teachers as a strategy for shaping students' religious moderation attitudes at Madrasah Ulumul Qur'an Langsa, focusing on the communication process, the values conveyed, and its supporting and inhibiting factors. Using a qualitative case study method, data were gathered through in-depth interviews, observations, and documentation. The findings reveal that teachers construct communication strategies through direct role-modeling (uswatun hasanah), personal dialogue, curriculum integration, and the application of Islamic communication principles (qaulan sadida, qaulan baligha, qaulan layyina). These strategies successfully foster tolerance, national commitment, anti-violence, and local cultural accommodation among students. Supporting factors include a conducive environment, teacher exemplary behavior, and an integrated curriculum, whereas inhibiting factors involve social media influence and diverse student backgrounds. This study contributes to Islamic communication literature by introducing communication construction as a strategic process for meaning-making and internalizing religious moderation values within a madrasah environment.